Relevansi antara self efficacy dengan kecemasan sebelum bertanding pada atlet futsal putri - Aliyyah, Aliyyah; Wicaksono, Bagus; Saniatuzzulfa, Rahmah; Mukholid, Agus (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
The athletes performance will be excellent with the support of healthy mind. Psychological state such as anxiety must be lessened to achieve the desired performance. Several previous studies suggest that anxiety is closely related to self-efficacy. Positive self-efficacy helps the athletes in controlling their anxiety. This study aims to determine the relationship between self-efficacy and anxiety before the match. The research involves 44 female futsal athletes of Sebelas Maret University in Surakarta. To measure the variables in this study, the anxiety scale before the match (reliability = 0.927) and self-efficacy scale (reliability = 0.859) are used. Hypothesis test result of r = -0.334 shows that there is a negative and significant relationship between self-efficacy and anxiety before the match, which means the lower self-efficacy, the higher athletes’ anxiety before the match (P = 0.023; p <0.05). This research is limited to female futsal athletes. Further studies are expected to involve male athletes and other sports.